Gel polymer modified ion exchange membrane, and preparation method and application thereof
By preparing a gel polymer-modified ion exchange membrane, the problems of high vanadium ion permeability and slow electrode reaction in vanadium redox flow batteries were solved by utilizing the synergistic effect of cationic monomers, anionic monomers and metal salts. This improved the coulombic efficiency and voltage efficiency of the battery and enhanced the puncture resistance of the membrane.
Patent Information
- Application Number
- CN202511706601.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-20
- Publication Date
- 2026-02-03
- Estimated Expiration
- 2045-11-20
AI Technical Summary
In vanadium redox flow batteries, the ion exchange membrane suffers from problems such as high vanadium ion permeability, slow electrode reaction kinetics, high polarization loss, low electrolyte concentration, and narrow temperature window, which lead to a decline in battery performance.
Gel polymer-modified ion exchange membranes were prepared using a mixed solution of cationic monomers, anionic monomers, nitrogen-containing monomers, crosslinking agents, and metal salts. A gel layer was formed on the membrane surface to inhibit vanadium ion permeation and improve ionic conductivity. Metal catalysts were electrodeposited in situ on the electrode surface to enhance electrode reactivity.
It effectively inhibits vanadium ion penetration, improves battery coulombic efficiency and voltage efficiency, enhances the membrane's puncture resistance, maintains stable battery operation, and improves current density and battery performance.
Smart Images

Figure CN121172211B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of vanadium redox flow battery membrane technology, and in particular to a gel polymer modified ion exchange membrane, its preparation method, and its application. Background Technology
[0002] High-power vanadium redox flow batteries (VFBs) are still limited by the high vanadium permeability of ion-exchange membranes, slow electrode reaction kinetics, high polarization losses, and high levelized cost per kilowatt-hour. In high-energy scenarios, low electrolyte concentration and narrow temperature windows result in low energy density and large size. Therefore, developing highly selective, low-cost membrane materials, constructing highly active, low-polarization electrode-flow field coupling structures, and coordinating with high-concentration, wide-temperature-range electrolyte formulations are the core technological bottlenecks for achieving high-proportion renewable energy consumption and supporting new power systems.
[0003] The membrane is one of the key components of VFB, and it must meet the requirements of active ions (H+). + H3O + SO4 2− SO4H − The high-speed diffusion of vanadium ions (VFB) results in minimal or no vanadium ion penetration. Active ions complete the current loop through membrane diffusion; however, vanadium ion penetration leads to pressure imbalance and self-discharge across the battery, thus reducing the coulombic efficiency of the VFB. An ideal membrane should possess high ion selectivity, exhibiting both high ionic conductivity and good vanadium barrier properties. With increasing demands on battery cost, fuel cell stacks require higher power densities, i.e., high current density operation. Existing technologies achieve higher current density requirements by thinning the ion exchange membrane and modifying the electrodes. However, thinning the ion exchange membrane leads to low ion selectivity, poor vanadium barrier properties, and reduced strength. Furthermore, modified electrodes can harden the graphite felt, making it prone to puncture when used with the ion exchange membrane, resulting in decreased membrane performance. Summary of the Invention
[0004] The purpose of this invention is to provide a method for preparing a gel polymer modified ion exchange membrane for vanadium redox flow batteries. This membrane has both low vanadium ion permeability and high ionic conductivity, and the gel polymer modified layer on the membrane surface can act as a buffer layer to prevent the membrane from being punctured by the electrode. When applied to vanadium redox flow batteries (VFB), it can effectively improve the performance.
[0005] In a first aspect, a method for preparing a gel polymer-modified ion exchange membrane is disclosed, comprising the following steps:
[0006] Step S1: Dissolve the cationic monomer, anionic monomer, nitrogen-containing monomer, crosslinking agent, metal salt and deionized water by stirring, and then introduce nitrogen gas to obtain a monomer solution;
[0007] Step S2: Dissolve the initiator and deionized water by stirring, then purge with nitrogen gas to obtain an initiator solution; dissolve the reducing agent and deionized water by stirring, then purge with nitrogen gas to obtain a reducing agent solution;
[0008] Step S3: Take the monomer solution, the initiator solution and the reducing agent solution, mix and stir to obtain a gel prepreg; coat the gel prepreg onto both sides of the ion exchange membrane, heat and solidify to obtain a modified ion exchange membrane;
[0009] Step S4: The modified ion exchange membrane is washed by immersing it in deionized water multiple times, and then immersed in dilute sulfuric acid solution to obtain a gel polymer modified ion exchange membrane.
[0010] In one implementation, in step S1:
[0011] The mass ratio of the cationic monomer, the anionic monomer, the nitrogen-containing monomer, the crosslinking agent, the metal salt, and the deionized water is (8~20):(2~5):(4~10):(0.5~2.5):(0.05~0.2):(65~85).
[0012] The cationic monomer is selected from at least one of dimethyl diallyl ammonium chloride, 1-allyl-3-vinylimidazolium chloride, methacryloyloxyethyltrimethylammonium chloride, and (3-acrylamidopropyl)trimethylammonium chloride;
[0013] Cationic monomers and nitrogen-containing monomers can polymerize to form a gel layer. The cations themselves have a positive charge, while the nitrogen-containing monomers combine with protons in the acidic electrolyte to form a positive charge. The two work together to effectively inhibit the shuttle penetration of vanadium ions in the positive and negative electrode electrolytes of vanadium batteries.
[0014] The anionic monomer is selected from at least one of 2-acrylamido-2-methyl-1-propanesulfonic acid, sodium p-styrenesulfonate, sodium methpropylenesulfonate, and sodium allylsulfonate.
[0015] Anionic monomers can polymerize to form a gel layer, exhibiting excellent proton conductivity in acidic vanadium battery electrolytes, which can effectively improve the conductivity of ion-exchange membranes.
[0016] The nitrogen-containing monomer is selected from at least one of vinylimidazole, N,N-dimethylallylamine, diallylamine, and N-methyldiallylamine;
[0017] The crosslinking agent is selected from any one of polyethylene glycol diacrylate, 1,6-bis(acryloyloxy)-2,2,3,3,4,4,5,5-octafluorohexane, N,N'-methylenebisacrylamide, and 1,3,5-triacryloyl-hexahydrotriazine.
[0018] Crosslinking agents crosslink and polymerize with cationic monomers, nitrogen-containing monomers, and anionic monomers to form a gel layer with a certain strength and elasticity on the surface of the ion exchange membrane. This forms an effective protective layer, preventing the ion exchange membrane from being punctured due to excessively hard electrodes or excessively high compression ratios, thus maintaining the normal and stable operation of the battery.
[0019] The metal salt is selected from at least one of bismuth chloride, copper sulfate, and silver nitrate.
[0020] During battery operation, metal ions can be slowly released into the electrode surface. During charging, metal ions are electrodeposited in situ on the electrode surface to form a metal catalyst, which can effectively increase the electrode reaction activity and improve the battery voltage efficiency.
[0021] In one implementation, in step S1:
[0022] The stirring and dissolving speed is 1000~3000 r / min, and the time is 1~2 h.
[0023] In one implementation, in step S2:
[0024] The mass ratio of initiator to deionized water in the initiator solution is (5~10):(90~95);
[0025] The initiator is selected from at least one of potassium persulfate and ammonium persulfate.
[0026] In one implementation, in step S2:
[0027] The mass ratio of reducing agent to deionized water in the reducing agent solution is (5~10):(90~95);
[0028] The reducing agent is selected from at least one of sodium bisulfite and sodium sulfite.
[0029] In one embodiment, the nitrogen gas is introduced for 30 minutes in step S2.
[0030] In one implementation, in step S3:
[0031] The mass ratio of the monomer solution, the initiator solution, and the reducing agent solution is (92.5~97):(2~5):(1~2.5);
[0032] The mixing and stirring speed is 500~1000 r / min, and the time is 20~40 s;
[0033] The thickness of the coating is 50~150μm;
[0034] The heating and curing temperature is 35~45℃, and the time is 10~30min.
[0035] In one implementation, in step S4:
[0036] The cleaning is performed 5 to 10 times, and the cleaning time is 1 to 2 hours.
[0037] The concentration of the dilute sulfuric acid solution is 0.2~0.6 mol / L;
[0038] The soaking time is 4 to 8 hours.
[0039] Secondly, a gel polymer modified ion exchange membrane is disclosed, which is prepared by the above-described method for preparing gel polymer modified ion exchange membranes.
[0040] Thirdly, an application of a gel polymer modified ion exchange membrane is disclosed, wherein the gel polymer modified ion exchange membrane prepared by the above preparation method or the above gel polymer modified ion exchange membrane is applied to an all-vanadium redox flow battery.
[0041] The beneficial effects of this invention are:
[0042] 1. The gel polymer modified ion exchange membrane of the present invention uses cationic monomers and nitrogen-containing monomers to prepare the gel layer. The cationic monomers themselves have positive charges, and the nitrogen-containing monomers combine with protons in the acidic electrolyte to form positive charges, which can effectively inhibit vanadium ion penetration and improve the coulombic efficiency of the battery.
[0043] 2. The gel polymer modified ion exchange membrane of the present invention uses anionic monomers to prepare the gel layer. The anionic monomers have excellent proton conductivity in acidic electrolytes, which can effectively improve ionic conductivity and improve battery voltage efficiency.
[0044] 3. The gel polymer modified ion exchange membrane of the present invention forms a gel layer with a certain strength and elasticity on the surface of the ion exchange membrane by cross-linking and polymerization of a cross-linking agent with cationic monomers, nitrogen-containing monomers and anionic monomers. It can form an effective protective layer to prevent the ion exchange membrane from being punctured due to excessively hard electrodes or excessively high compression ratio, and maintain the normal and stable operation of the battery.
[0045] 4. The gel polymer modified ion exchange membrane of the present invention is prepared by adding metal salt to the monomer solution to obtain a gel layer in which metal salt is uniformly dispersed. During battery operation, metal ions can be slowly released into the electrode surface. During charging, metal ions are electrodeposited in situ on the electrode surface to form a metal catalyst, which can effectively increase the electrode reaction activity and improve the voltage efficiency of the battery. Attached Figure Description
[0046] Figure 1 This is a schematic flowchart of a method for preparing a gel polymer-modified ion exchange membrane for an all-vanadium redox flow battery according to the present invention.
[0047] Figure 2 These are the EDX spectra of the blank ion exchange membrane in Comparative Example 1 and the gel polymer modified ion exchange membrane in Example 1 of this invention.
[0048] Figure 3 This is a cross-sectional SEM image of the gel polymer-modified ion exchange membrane of Example 1 of the present invention. Detailed Implementation
[0049] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. However, it should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the scope of the invention. Furthermore, descriptions of well-known structures and technologies are omitted in the following description to avoid unnecessarily obscuring the concept of the invention.
[0050] See Figure 1 This invention discloses a method for preparing a gel polymer-modified ion exchange membrane, comprising the following steps: First, a monomer solution is prepared by mixing a cationic monomer, an anionic monomer, a nitrogen-containing monomer, a crosslinking agent, a metal salt, and deionized water; second, an initiator and a reducing agent are respectively mixed with pure water to prepare initiator and reducing agent solutions; further, a gel prepreg prepared by mixing the monomer solution, initiator solution, and reducing agent solution is coated onto both sides of an ion exchange membrane to prepare a modified ion exchange membrane; finally, the modified ion exchange membrane is washed and soaked in dilute sulfuric acid to obtain a gel polymer-modified ion exchange membrane.
[0051] Example 1: The following technical solution is adopted.
[0052] Step S1: Monomer solution preparation: Take 8 parts by mass of dimethyl diallyl ammonium chloride, 2 parts by mass of 2-acrylamido-2-methyl-1-propanesulfonic acid, 4 parts by mass of vinylimidazole, 0.5 parts by mass of polyethylene glycol diacrylate, 0.05 parts by mass of bismuth chloride, and 65 parts by mass of deionized water, stir at 1000 r / min for 1 h, and purge with nitrogen gas for 30 min to obtain the monomer solution.
[0053] Step S2: Preparation of initiator and reducing agent solutions: Take 5 parts by mass of potassium persulfate and 90 parts by mass of deionized water, stir to dissolve, and purge with nitrogen for 30 min to obtain initiator solution; take 5 parts by mass of sodium bisulfite and 90 parts by mass of deionized water, stir to dissolve, and purge with nitrogen for 30 min to obtain reducing agent solution.
[0054] Step S3: Gel polymer modified ion exchange membrane: Take 92.5 parts by mass of monomer solution, 2 parts by mass of initiator solution and 1 part by mass of reducing agent solution, mix and stir at 500 r / min for 20 s to obtain gel prepreg; apply gel prepreg to both sides of ion exchange membrane with a coating height of 50 μm, heat and cure at 35℃ for 10 min to obtain modified ion exchange membrane.
[0055] Step S4: Post-treatment of modified ion exchange membrane: Soak the modified ion exchange membrane in deionized water for 5 washes, 1 hour each time, and then soak it in 0.2 mol / L dilute sulfuric acid solution for 4 hours to obtain gel polymer modified ion exchange membrane.
[0056] Figure 2 The Bi element distribution diagrams for Comparative Example 1 and this embodiment show that the Bi element content is higher in this embodiment, while Comparative Example 1 does not contain Bi element, indicating that a gel layer with uniformly dispersed Bi element is formed on the ion exchange membrane prepared in this embodiment.
[0057] Figure 3 The image shows a cross-sectional SEM image of the ion exchange membrane prepared in this embodiment, which reveals the presence of a gel layer on the membrane surface.
[0058] Example 2: The following technical solution is adopted.
[0059] Step S1: Monomer solution preparation: Take 12 parts by mass of 1-allyl-3-vinylimidazolium chloride, 3 parts by mass of sodium p-styrenesulfonate, 6 parts by mass of N,N-dimethylallylamine, 1 part by mass of 1,6-bis(acryloyloxy)-2,2,3,3,4,4,5,5-octafluorohexane, 0.1 parts by mass of copper sulfate and 70 parts by mass of deionized water, stir at 1500 r / min for 1.3 h, and purge with nitrogen for 30 min to obtain the monomer solution;
[0060] Step S2: Preparation of initiator and reducing agent solutions: Take 7 parts by mass of ammonium persulfate and 92 parts by mass of deionized water, stir to dissolve, and purge with nitrogen for 30 min to obtain initiator solution; Take 6 parts by mass of sodium sulfite and 91 parts by mass of deionized water, stir to dissolve, and purge with nitrogen for 30 min to obtain reducing agent solution;
[0061] Step S3: Gel polymer modified ion exchange membrane: Take 94.5 parts by mass of monomer solution, 3 parts by mass of initiator solution and 1.5 parts by mass of reducing agent solution, mix and stir at 650 r / min for 25 s to obtain gel prepreg. Apply the gel prepreg to both sides of the ion exchange membrane with a coating height of 80 μm, heat and cure at 38℃ for 15 min to obtain the modified ion exchange membrane;
[0062] Step S4: Post-treatment of modified ion exchange membrane: Immerse the modified ion exchange membrane in deionized water for 6 washes, 1.3 h each time, and then immerse it in 0.3 mol / L dilute sulfuric acid solution for 5 h to obtain gel polymer modified ion exchange membrane.
[0063] Example 3: The following technical solution is adopted.
[0064] Step S1: Monomer solution preparation: Take 16 parts by mass of methacryloyloxyethyltrimethylammonium chloride, 4 parts by mass of sodium methacrylate sulfonate, 8 parts by mass of diallylamine, 2 parts by mass of N,N'-methylenebisacrylamide, 0.15 parts by mass of silver nitrate and 80 parts by mass of deionized water, stir at 2500 r / min for 1.7 h to dissolve, and then purge with nitrogen gas for 30 min to obtain the monomer solution;
[0065] Step S2: Preparation of initiator and reducing agent solutions: Take 9 parts by mass of potassium persulfate and 94 parts by mass of deionized water, stir to dissolve, and purge with nitrogen for 30 min to obtain initiator solution; Take 8 parts by mass of sodium bisulfite and 93 parts by mass of deionized water, stir to dissolve, and purge with nitrogen for 30 min to obtain reducing agent solution;
[0066] Step S3: Gel polymer modified ion exchange membrane: Take 95.5 parts by mass of monomer solution, 4 parts by mass of initiator solution and 2 parts by mass of reducing agent solution, mix and stir at 850 r / min for 35 s to obtain gel prepreg; apply gel prepreg to both sides of ion exchange membrane with a coating height of 120 μm, heat and cure at 42℃ for 25 min to obtain modified ion exchange membrane;
[0067] Step S4: Post-treatment of modified ion exchange membrane: Immerse the modified ion exchange membrane in deionized water for 8 washes, 1.7 h each time, and then immerse it in 0.5 mol / L dilute sulfuric acid solution for 7 h to obtain gel polymer modified ion exchange membrane.
[0068] Example 4: The following technical solution is adopted.
[0069] Step S1: Monomer solution preparation: Take 20 parts by mass of (3-acrylamidopropyl)trimethylammonium chloride, 5 parts by mass of sodium allyl sulfonate, 10 parts by mass of N-methyldiallylamine, 2.5 parts by mass of 1,3,5-triacryloyl-hexahydrotriazine, 0.2 parts by mass of bismuth chloride and 85 parts by mass of deionized water, stir at 3000 r / min for 2 h to dissolve, and then purge with nitrogen gas for 30 min to obtain the monomer solution;
[0070] Step S2: Preparation of initiator and reducing agent solutions: Take 10 parts by mass of ammonium persulfate and 95 parts by mass of deionized water, stir to dissolve, and purge with nitrogen for 30 min to obtain initiator solution; Take 10 parts by mass of sodium sulfite and 95 parts by mass of deionized water, stir to dissolve, and purge with nitrogen for 30 min to obtain reducing agent solution;
[0071] Step S3: Gel polymer modified ion exchange membrane: Take 97 parts by mass of monomer solution, 5 parts by mass of initiator solution and 2.5 parts by mass of reducing agent solution, mix and stir at 1000 r / min for 40 s to obtain gel prepreg. Apply the gel prepreg to both sides of the ion exchange membrane with a coating height of 150 μm, heat and cure at 45℃ for 30 min to obtain modified ion exchange membrane;
[0072] Step S4: Post-treatment of modified ion exchange membrane: Immerse the modified ion exchange membrane in deionized water for 10 washes, 2 hours each time, and then immerse it in 0.6 mol / L dilute sulfuric acid solution for 8 hours to obtain gel polymer modified ion exchange membrane.
[0073] Comparative Example 1: The following technical solution is adopted.
[0074] Blank ion exchange membrane without any treatment.
[0075] Comparative Example 2: The following technical solution is adopted.
[0076] The only difference from Example 1 is that no anionic monomer is added in step S1;
[0077] Step S1: Monomer solution preparation: Take 8 parts by mass of dimethyl diallyl ammonium chloride, 4 parts by mass of vinylimidazole, 0.5 parts by mass of polyethylene glycol diacrylate and 65 parts by mass of deionized water, stir and dissolve at 1000 r / min for 1 h, and purge with nitrogen for 30 min to obtain monomer solution;
[0078] Step S2: Preparation of initiator and reducing agent solutions: Take 5 parts by mass of potassium persulfate and 90 parts by mass of deionized water, stir to dissolve, and purge with nitrogen for 30 min to obtain the initiator solution; Take 5 parts by mass of sodium bisulfite and 90 parts by mass of deionized water, stir to dissolve, and purge with nitrogen for 30 min to obtain the reducing agent solution;
[0079] Step S3: Gel polymer modified ion exchange membrane: Take 92.5 parts by mass of monomer solution, 2 parts by mass of initiator solution and 1 part by mass of reducing agent solution, mix and stir at 500 r / min for 20 s to obtain gel prepreg; apply gel prepreg to both sides of ion exchange membrane with a coating height of 50 μm, heat and cure at 35℃ for 10 min to obtain modified ion exchange membrane;
[0080] Step S4: Post-treatment of modified ion exchange membrane: Soak the S3 modified ion exchange membrane in deionized water for 5 washes, 1 hour each time, and then soak it in 0.2 mol / L dilute sulfuric acid solution for 4 hours to obtain gel polymer modified ion exchange membrane.
[0081] Comparative Example 3: The following technical solution is adopted.
[0082] The only difference from Example 1 is that no metal salt is added in step S1;
[0083] Step S1: Monomer solution preparation: Take 8 parts by mass of dimethyl diallyl ammonium chloride, 2 parts by mass of 2-acrylamido-2-methyl-1-propanesulfonic acid, 4 parts by mass of vinylimidazole, 0.5 parts by mass of polyethylene glycol diacrylate and 65 parts by mass of deionized water, stir at 1000 r / min for 1 h, and purge with nitrogen for 30 min to obtain monomer solution;
[0084] Step S2: Preparation of initiator and reducing agent solutions: Take 5 parts by mass of potassium persulfate and 90 parts by mass of deionized water, stir to dissolve, and purge with nitrogen for 30 min to obtain the initiator solution; Take 5 parts by mass of sodium bisulfite and 90 parts by mass of deionized water, stir to dissolve, and purge with nitrogen for 30 min to obtain the reducing agent solution;
[0085] Step S3: Gel polymer modified ion exchange membrane: Take 92.5 parts by mass of monomer solution, 2 parts by mass of initiator solution and 1 part by mass of reducing agent solution, mix and stir at 500 r / min for 20 s to obtain gel prepreg; apply gel prepreg to both sides of ion exchange membrane with a coating height of 50 μm, heat and cure at 35℃ for 10 min to obtain modified ion exchange membrane;
[0086] Step S4: Post-treatment of modified ion exchange membrane: Soak the modified ion exchange membrane in deionized water for 5 washes, 1 hour each time, and then soak it in 0.2 mol / L dilute sulfuric acid solution for 4 hours to obtain gel polymer modified ion exchange membrane.
[0087] Comparative Example 4: The following technical solution is adopted.
[0088] The only difference from Example 1 is that no crosslinking agent and metal salt are added in step S1;
[0089] Step S1: Monomer solution preparation: Take 8 parts by mass of dimethyl diallyl ammonium chloride, 2 parts by mass of 2-acrylamido-2-methyl-1-propanesulfonic acid, 4 parts by mass of vinylimidazole and 65 parts by mass of deionized water, stir and dissolve at 1000 r / min for 1 h, and purge with nitrogen for 30 min to obtain monomer solution.
[0090] Step S2: Preparation of initiator and reducing agent solutions: Take 5 parts by mass of potassium persulfate and 90 parts by mass of deionized water, stir to dissolve, and purge with nitrogen for 30 min to obtain the initiator solution; Take 5 parts by mass of sodium bisulfite and 90 parts by mass of deionized water, stir to dissolve, and purge with nitrogen for 30 min to obtain the reducing agent solution;
[0091] Step S3: Gel polymer modified ion exchange membrane: Take 92.5 parts by mass of monomer solution, 2 parts by mass of initiator solution and 1 part by mass of reducing agent solution, mix and stir at 500 r / min for 20 s to obtain gel prepreg; apply gel prepreg to both sides of ion exchange membrane with a coating height of 50 μm, heat and cure at 35℃ for 10 min to obtain modified ion exchange membrane;
[0092] Step S4: Post-treatment of modified ion exchange membrane: Soak the S3 modified ion exchange membrane in deionized water for 5 washes, 1 hour each time, and then soak it in 0.2 mol / L dilute sulfuric acid solution for 4 hours to obtain gel polymer modified ion exchange membrane.
[0093] Comparative Example 5: The following technical solution is adopted.
[0094] The only difference from Example 1 is that the amount of crosslinking agent polyethylene glycol diacrylate added in step S1 is 0.1 parts by weight;
[0095] Step S1: Monomer solution preparation: Take 8 parts by mass of dimethyl diallyl ammonium chloride, 2 parts by mass of 2-acrylamido-2-methyl-1-propanesulfonic acid, 4 parts by mass of vinylimidazole, 0.1 parts by mass of polyethylene glycol diacrylate, 0.05 parts by mass of bismuth chloride, and 65 parts by mass of deionized water, stir at 1000 r / min for 1 h, and purge with nitrogen gas for 30 min to obtain the monomer solution.
[0096] Step S2: Preparation of initiator and reducing agent solutions: Take 5 parts by mass of potassium persulfate and 90 parts by mass of deionized water, stir to dissolve, and purge with nitrogen for 30 min to obtain initiator solution; take 5 parts by mass of sodium bisulfite and 90 parts by mass of deionized water, stir to dissolve, and purge with nitrogen for 30 min to obtain reducing agent solution.
[0097] Step S3: Gel polymer modified ion exchange membrane: Take 92.5 parts by mass of monomer solution, 2 parts by mass of initiator solution and 1 part by mass of reducing agent solution, mix and stir at 500 r / min for 20 s to obtain gel prepreg; apply gel prepreg to both sides of ion exchange membrane with a coating height of 50 μm, heat and cure at 35℃ for 10 min to obtain modified ion exchange membrane.
[0098] Step S4: Post-treatment of modified ion exchange membrane: Soak the modified ion exchange membrane in deionized water for 5 washes, 1 hour each time, and then soak it in 0.2 mol / L dilute sulfuric acid solution for 4 hours to obtain gel polymer modified ion exchange membrane.
[0099] Comparative Example 6: The following technical solution was adopted.
[0100] The only difference from Example 1 is that the amount of crosslinking agent polyethylene glycol diacrylate added in step S1 is 3 parts by mass;
[0101] Step S1: Monomer solution preparation: Take 8 parts by mass of dimethyl diallyl ammonium chloride, 2 parts by mass of 2-acrylamido-2-methyl-1-propanesulfonic acid, 4 parts by mass of vinylimidazole, 3 parts by mass of polyethylene glycol diacrylate, 0.05 parts by mass of bismuth chloride, and 65 parts by mass of deionized water, stir at 1000 r / min for 1 h, and purge with nitrogen gas for 30 min to obtain the monomer solution.
[0102] Step S2: Preparation of initiator and reducing agent solutions: Take 5 parts by mass of potassium persulfate and 90 parts by mass of deionized water, stir to dissolve, and purge with nitrogen for 30 min to obtain initiator solution; take 5 parts by mass of sodium bisulfite and 90 parts by mass of deionized water, stir to dissolve, and purge with nitrogen for 30 min to obtain reducing agent solution.
[0103] Step S3: Gel polymer modified ion exchange membrane: Take 92.5 parts by mass of monomer solution, 2 parts by mass of initiator solution and 1 part by mass of reducing agent solution, mix and stir at 500 r / min for 20 s to obtain gel prepreg; apply gel prepreg to both sides of ion exchange membrane with a coating height of 50 μm, heat and cure at 35℃ for 10 min to obtain modified ion exchange membrane.
[0104] Step S4: Post-treatment of modified ion exchange membrane: Soak the modified ion exchange membrane in deionized water for 5 washes, 1 hour each time, and then soak it in 0.2 mol / L dilute sulfuric acid solution for 4 hours to obtain gel polymer modified ion exchange membrane.
[0105] Comparative Example 7: The following technical solution was adopted.
[0106] The only difference from Example 1 is that the amount of bismuth chloride metal salt added in step S1 is 0.03 parts by mass;
[0107] Step S1: Monomer solution preparation: Take 8 parts by mass of dimethyl diallyl ammonium chloride, 2 parts by mass of 2-acrylamido-2-methyl-1-propanesulfonic acid, 4 parts by mass of vinylimidazole, 0.5 parts by mass of polyethylene glycol diacrylate, 0.03 parts by mass of bismuth chloride, and 65 parts by mass of deionized water, stir at 1000 r / min for 1 h, and purge with nitrogen gas for 30 min to obtain the monomer solution.
[0108] Step S2: Preparation of initiator and reducing agent solutions: Take 5 parts by mass of potassium persulfate and 90 parts by mass of deionized water, stir to dissolve, and purge with nitrogen for 30 min to obtain initiator solution; take 5 parts by mass of sodium bisulfite and 90 parts by mass of deionized water, stir to dissolve, and purge with nitrogen for 30 min to obtain reducing agent solution.
[0109] Step S3: Gel polymer modified ion exchange membrane: Take 92.5 parts by mass of monomer solution, 2 parts by mass of initiator solution and 1 part by mass of reducing agent solution, mix and stir at 500 r / min for 20 s to obtain gel prepreg; apply gel prepreg to both sides of ion exchange membrane with a coating height of 50 μm, heat and cure at 35℃ for 10 min to obtain modified ion exchange membrane.
[0110] Step S4: Post-treatment of modified ion exchange membrane: Soak the modified ion exchange membrane in deionized water for 5 washes, 1 hour each time, and then soak it in 0.2 mol / L dilute sulfuric acid solution for 4 hours to obtain gel polymer modified ion exchange membrane.
[0111] Comparative Example 8: The following technical solution is adopted.
[0112] The only difference from Example 1 is that the amount of bismuth chloride metal salt added in step S1 is 0.3 parts by mass;
[0113] Step S1: Monomer solution preparation: Take 8 parts by mass of dimethyl diallyl ammonium chloride, 2 parts by mass of 2-acrylamido-2-methyl-1-propanesulfonic acid, 4 parts by mass of vinylimidazole, 0.5 parts by mass of polyethylene glycol diacrylate, 0.3 parts by mass of bismuth chloride, and 65 parts by mass of deionized water, stir at 1000 r / min for 1 h, and purge with nitrogen gas for 30 min to obtain the monomer solution.
[0114] Step S2: Preparation of initiator and reducing agent solutions: Take 5 parts by mass of potassium persulfate and 90 parts by mass of deionized water, stir to dissolve, and purge with nitrogen for 30 min to obtain initiator solution; take 5 parts by mass of sodium bisulfite and 90 parts by mass of deionized water, stir to dissolve, and purge with nitrogen for 30 min to obtain reducing agent solution.
[0115] Step S3: Gel polymer modified ion exchange membrane: Take 92.5 parts by mass of monomer solution, 2 parts by mass of initiator solution and 1 part by mass of reducing agent solution, mix and stir at 500 r / min for 20 s to obtain gel prepreg; apply gel prepreg to both sides of ion exchange membrane with a coating height of 50 μm, heat and cure at 35℃ for 10 min to obtain modified ion exchange membrane.
[0116] Step S4: Post-treatment of modified ion exchange membrane: Soak the modified ion exchange membrane in deionized water for 5 washes, 1 hour each time, and then soak it in 0.2 mol / L dilute sulfuric acid solution for 4 hours to obtain gel polymer modified ion exchange membrane.
[0117] Experimental Procedure and Data:
[0118] 1. Proton conductivity test of ion exchange membrane: The inner chamber of the conductivity cell is moistened with a 3.0 mol / L sulfuric acid aqueous solution. The two halves of the conductivity cell are joined together and clamped tightly with an iron clamp. A 3.0 mol / L sulfuric acid aqueous solution is added dropwise to the liquid inlet of the conductivity cell using a dropper, removing any bubbles. The test leads of the counter electrode and reference electrode of the electrochemical workstation are simultaneously clamped onto the electrode at one end of the conductivity cell, and the test lead of the working electrode is clamped onto the electrode at the other end of the conductivity cell. The impedance of the multiple cell is measured. After the test, the resistance value in the high-frequency region intersecting the real axis is read, which is the blank impedance R1 of the conductivity cell. Membrane sheets of a certain size (15 mm × 15 mm) from the examples and comparative examples are immersed in a 3.0 mol / L sulfuric acid aqueous solution and allowed to stand at room temperature for 24 hours. The pretreated membrane sample is clamped between the two halves of the conductivity testing device, and the impedance R2 of the conductivity cell of the membrane sample is measured using the electrochemical workstation. Repeat the measurement three times, record all impedance data and calculate the average value, denoted as `R1, `R2. The membrane conductivity k = d / (`R2 A - `R1A), where d is the average thickness of the membrane, A is the effective area of the membrane, `R1 is the impedance value of the conductivity cell without the membrane sample, and `R2 is the impedance value of the conductivity cell with the membrane sample installed.
[0119] 2. Ion exchange membrane self-discharge test: The membrane is assembled into a single cell, connected to the test cabinet, and subjected to a test at 100 mA / cm². 2 At the specified current density, the battery capacity was charged to 50% SOC, the process was set to rest, and the voltage was recorded. The process was stopped when the battery voltage reached the cutoff voltage of 0.8V. The rest time is the battery's self-discharge time. Self-discharge performance is an important parameter for evaluating the vanadium blocking properties of ion-conducting membranes. The cause of battery self-discharge is the interpenetration of vanadium ions of different valence states through the membrane on both the positive and negative electrodes. The longer the self-discharge time, the better the vanadium blocking performance of the membrane.
[0120] 3. Puncture resistance test of ion exchange membrane: The puncture resistance of the ion exchange membranes obtained by the test examples and comparative examples were tested in accordance with GB / T 37841-2019 "Test method for puncture resistance of plastic films and sheets".
[0121] 4. Battery Testing: The ion exchange membranes prepared in the examples and comparative examples were assembled into single-cell stacks and subjected to charge-discharge tests under the same test conditions. The test charge-discharge current density was 150 mA / cm². 2 The battery coulombic efficiency, voltage efficiency, and energy efficiency were recorded, and the test results are shown in Table 1.
[0122] Table 1. Test results of charge / discharge, self-discharge, and proton conductivity.
[0123]
[0124] As shown in Table 1, Comparative Example 1, the blank ion exchange membrane without any treatment, exhibits relatively low single-cell charge-discharge coulombic efficiency, voltage efficiency, and energy efficiency. Comparative Example 2, compared to Comparative Example 1, uses an additional cationic monomer, nitrogen-containing monomer, and crosslinking agent to prepare a gel polymer layer modified ion exchange membrane. Its charge-discharge test shows higher coulombic efficiency and longer self-discharge time, indicating that the gel polymer modified ion exchange membrane uses cationic and nitrogen-containing monomers to prepare the gel layer. The cationic monomers themselves possess a positive charge, and the nitrogen-containing monomers combine with protons in the acidic electrolyte to form a positive charge, effectively inhibiting vanadium ion penetration and improving battery coulombic efficiency. Comparative Example 3, compared to Comparative Example 2, adds anionic monomers during the monomer solution preparation process, resulting in only a slight decrease in coulombic efficiency and a significant increase in voltage efficiency and ionic conductivity. This indicates that the gel polymer modified ion exchange membrane uses anionic monomers to prepare the gel layer. The anionic monomers possess excellent proton conductivity in the acidic electrolyte, effectively improving ionic conductivity and battery voltage efficiency. Compared to Comparative Example 4, Comparative Example 3 added a crosslinking agent during the monomer solution preparation process, forming a stable gel-modified layer. In contrast, Comparative Example 4 did not add a crosslinking agent during monomer solution preparation, causing the ion exchange membrane to dissolve and detach during washing and soaking in dilute sulfuric acid, failing to form a stable gel-modified layer. When tested with a harder modified graphite felt, it exhibited lower coulombic efficiency and shorter self-discharge time. This indicates that the gel polymer-modified ion exchange membrane, through crosslinking polymerization of the crosslinking agent with cationic monomers, nitrogen-containing monomers, and anionic monomers, forms a gel layer of a certain strength and elasticity on the ion exchange membrane surface. This forms an effective protective layer, preventing the ion exchange membrane from being punctured due to excessively hard electrodes or excessively high compressibility, thus maintaining the normal and stable operation of the battery. Furthermore, the results of Example 1 and Comparative Examples 5 and 6 show that excessive or insufficient crosslinking agent usage will adversely affect the membrane's puncture resistance and conductivity, leading to poor overall membrane performance. The amount of crosslinking agent needs to be controlled within the limits specified in this application. Examples 1-4, compared to Comparative Example 1, combined the beneficial effects of Comparative Examples 2 and 3. Furthermore, the addition of metal salts to the monomer solution significantly improved the voltage efficiency of the single-cell charge-discharge test. This demonstrates that the gel polymer-modified ion exchange membrane, by adding metal salts to the monomer solution, prepares a uniformly dispersed metal salt gel layer. During battery operation, metal ions can be slowly released into the electrode surface. During charging, metal ions are in-situ electrodeposited on the electrode surface to form a metal catalyst, effectively increasing electrode reactivity and improving battery voltage efficiency. The results of Example 1 and Comparative Examples 7 and 8 show that the amount of metal salt added also affects membrane performance. Too little metal salt does not achieve a significant improvement, while excessive metal deposition alters the electrode microstructure, causing the electrode surface to become rough and potentially clogging electrode pores, affecting electrolyte diffusion and ion transport.
[0125] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions or improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing a gel polymer-modified ion exchange membrane, characterized in that, Specifically, the steps include the following: Step S1: Dissolve the cationic monomer, anionic monomer, nitrogen-containing monomer, crosslinking agent, metal salt, and deionized water by stirring, and purge with nitrogen gas to obtain a monomer solution; the mass ratio of the cationic monomer, the anionic monomer, the nitrogen-containing monomer, the crosslinking agent, the metal salt, and the deionized water is (8~20):(2~5):(4~10):(0.5~2.5):(0.05~0.2):(65~85); the cationic monomer is selected from at least one of dimethyl diallyl ammonium chloride, 1-allyl-3-vinylimidazolium chloride, methacryloyloxyethyltrimethylammonium chloride, and (3-acrylamidopropyl)trimethylammonium chloride. The anionic monomer is selected from at least one of 2-acryloylamino-2-methyl-1-propanesulfonic acid, sodium p-styrene sulfonate, sodium methpropylene sulfonate, and sodium allyl sulfonate; the nitrogen-containing monomer is selected from at least one of vinylimidazole, N,N-dimethylallylamine, diallylamine, and N-methyldiallylamine; the crosslinking agent is selected from at least one of polyethylene glycol diacrylate, 1,6-bis(acryloyloxy)-2,2,3,3,4,4,5,5-octafluorohexane, N,N'-methylenebisacrylamide, and 1,3,5-triacryloyl-hexahydrotriazine; the metal salt is selected from at least one of bismuth chloride, copper sulfate, and silver nitrate. Step S2: Dissolve the initiator and deionized water by stirring, then purge with nitrogen gas to obtain an initiator solution; dissolve the reducing agent and deionized water by stirring, then purge with nitrogen gas to obtain a reducing agent solution; Step S3: Take the monomer solution, the initiator solution and the reducing agent solution, mix and stir to obtain a gel prepreg; coat the gel prepreg onto both sides of the ion exchange membrane, heat and solidify to obtain a modified ion exchange membrane; Step S4: The modified ion exchange membrane is rinsed by immersing it in deionized water multiple times, and then immersed in dilute sulfuric acid solution to obtain a gel polymer modified ion exchange membrane.
2. The preparation method according to claim 1, characterized in that, In step S1: The stirring and dissolving speed is 1000~3000 r / min, and the time is 1~2 h.
3. The preparation method according to claim 1, characterized in that, In step S2: The mass ratio of initiator to deionized water in the initiator solution is (5~10):(90~95); The initiator is selected from at least one of potassium persulfate and ammonium persulfate.
4. The preparation method according to claim 1, characterized in that, In step S2: The mass ratio of reducing agent to deionized water in the reducing agent solution is (5~10):(90~95); The reducing agent is selected from at least one of sodium bisulfite and sodium sulfite.
5. The preparation method according to claim 1, characterized in that, The nitrogen gas is introduced for 30 minutes in step S2.
6. The preparation method according to claim 1, characterized in that, In step S3: The mass ratio of the monomer solution, the initiator solution, and the reducing agent solution is (92.5~97):(2~5):(1~2.5); The mixing and stirring speed is 500~1000 r / min, and the time is 20~40 s; The thickness of the coating is 50~150μm; The heating and curing temperature is 35~45℃, and the time is 10~30min.
7. The preparation method according to claim 1, characterized in that, In step S4: The cleaning is performed 5 to 10 times, and the time is 1 to 2 hours. The concentration of the dilute sulfuric acid solution is 0.2~0.6 mol / L; The soaking time is 4 to 8 hours.
8. A gel polymer modified ion exchange membrane, wherein the gel polymer modified ion exchange membrane is prepared by the preparation method of the gel polymer modified ion exchange membrane according to any one of claims 1-7.
9. An application of a gel polymer-modified ion exchange membrane, characterized in that, The gel polymer modified ion exchange membrane prepared by the preparation method according to any one of claims 1-7 or the gel polymer modified ion exchange membrane according to claim 8 is applied to a vanadium redox flow battery.
Citation Information
Patent Citations
Ion exchange membranes selectively permeable to specific ions
CN105102127A
Zwitter Nafion ion exchange membrane for vanadium batteries and preparation method thereof
CN108695534A